2017
DOI: 10.1177/0013916517715296
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Barriers to Energy Conservation Behavior: The Role of Worldviews and Climate Change Risk Perception

Abstract: We proposed and tested a conceptual model of how cultural cognition worldviews, climate change risk perception, and psychological barriers are related to reported energy conservation behavior frequency. Egalitarian and communitarian worldviews were correlated with heightened climate change risk perception, and egalitarian worldviews were correlated with weaker perceived barriers to reported energy conservation behavior. Heightened climate change risk perception was, in turn, associated with fewer perceived bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 67 publications
7
74
0
3
Order By: Relevance
“…Gifford and Chen () found that when consumer discredits the information regarding an environmental threat, they are less prone to climate change mitigation through a responsible food choice. Similarly, Lacroix and Gifford () reported an inverse relation between denial of the problem and energy conservation behaviour.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Gifford and Chen () found that when consumer discredits the information regarding an environmental threat, they are less prone to climate change mitigation through a responsible food choice. Similarly, Lacroix and Gifford () reported an inverse relation between denial of the problem and energy conservation behaviour.…”
Section: Introductionmentioning
confidence: 78%
“…In many studies (e.g., Gruber & Schlegelmilch, ; Lorenzoni et al, ; McGregor, ; Stich & Wagner, ; Stoll‐Kleemann et al, ) mechanisms were proposed to decrease responsible consumption but only a few studies provided empirical evidence. Recently, Gifford and his colleagues (Gifford & Chen, ; Lacroix & Gifford, ) reported a direct relationship between barriers and climate change mitigation behaviours. However, the results of the current study show that psychological barriers impede responsible consumption (e.g., energy conservation) indirectly by hindering moral norms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there has been a growing literature on policy implementation to deter and mitigate the negative externalities of climate change. More specifically, public perceptions of environmental issues and the public's level of concern have been found to be an important determinant of the effectiveness of climate change-related policies [6]. However, despite researchers' and policy makers' emphasis of the importance of climate change, the level of public concern is not equally heightened throughout the world [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Psychologists have addressed both the distance issue and the experience of risk as drivers of the public adaptation of pro-environment behavior [6][7][8].…”
Section: Introductionmentioning
confidence: 99%